Справочная книга рыболова-любителя - Вейшторд И. П. (Агропромиздат, 1992)
Экземпляры: ХР (20180704) / Инвентарный номер: 30399 / Цена: 81 / Сис.шифр: 47.2 / Авт.знак: С 74 / ГРНТИ: 68 / ББК: 47.226 я22